Applying a Strengths-Based Psychoeducational Model of Rehabilitation to the Treatment of Intimate Partner Violence: Program Theory and Logic Model. (February 2019) - Bowen, Erica; Walker, Kate; Holdsworth, Emma
In the United Kingdom, there is an increasing need to develop prevention programs for intimate partner violence and abuse (IPVA). However, this need has increased within a context of increasing financial pressure. Consequently, commissioners are expressing interest in models of prevention that are brief. This article first reviews the effectiveness of domestic violence (DV) prevention programs, including those from England and Wales. This article then describes the theoretical development of an emerging IPVA prevention program that combines solution-focused brief therapy (SFBT) and cognitive behavioral therapy (CBT) methods. The article addresses how CBT content is integrated within the SFBT approach and provides details of the intervention logic model.